Penerapan Algoritma Arithmetic Coding Pada Kompresi File Video Streaming Berbasis Android - Situmorang, Cathrin Desri Natalia (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
Streaming is a service that transmits video and audio over the internet. In this application, users can obtain video files such as movies by downloading or installing them through Android. However, downloading video files with a considerable duration can increase the usage capacity on Android storage, and sending such files may require a long time. To address this issue, it is necessary to compress the downloaded video files using one of the algorithms available in compression. Compression is a process of transforming a set of data into a code or symbol to save storage space and prevent the file size from becoming too large. Many algorithms have been developed in the compression process, one of which is the arithmetic coding algorithm. Arithmetic coding is a lossless compression technique, meaning it produces data that is identical to the original and does not lose information during compression and decompression processes. By using the arithmetic coding algorithm, the system achieves a Compression Ratio performance of (2.5), Compression Ratio of (40%), space saving of (60%), and Redundancy of (60%).